Entrepreneur cerdas, risiko terkendali: membangun bisnis berbasis perencanaan risiko - Salsabila, Zakiya (Maliki Interdisciplinary Journal, 2025)
In today’s highly uncertain business environment, risk management has become a critical competency for entrepreneurs. This article discusses the importance of risk management as a strategic foundation for designing and developing adaptive and sustainable businesses. By applying a four-stage approach—identification, analysis, mitigation, and monitoring—risk management provides a systematic framework for entrepreneurs to detect potential threats, assess their impacts, design appropriate responses, and continuously evaluate their effectiveness. The discussion includes common types of risks faced in business, such as financial, operational, market, legal, and technological risks. The article highlights the necessity of building business resilience and adaptability in responding to rapid change, while also addressing the benefits and challenges of risk management implementation, especially for micro, small, and medium enterprises (MSMEs). Finally, it offers practical solutions to help entrepreneurs apply risk management in a simple yet effective manner that aligns with their business scale. This approach positions risk management not merely as a defensive tool, but as a strategic driver for informed decision-making.